2022
DOI: 10.3390/cells12010067
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Lung Damage and Development of COPD Due to Household Biomass-Smoke Exposure: Inflammation, Oxidative Stress, MicroRNAs, and Gene Polymorphisms

Abstract: Chronic exposure to indoor biomass smoke from the combustion of solid organic fuels is a major cause of disease burden worldwide. Almost 3 billion people use solid fuels such as wood, charcoal, and crop residues for indoor cooking and heating, accounting for approximately 50% of all households and 90% of rural households globally. Biomass smoke contains many hazardous pollutants, resulting in household air pollution (HAP) exposure that often exceeds international standards. Long-term biomass-smoke exposure is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 195 publications
0
22
0
3
Order By: Relevance
“…Our results contrast to a previous study, in which higher levels of IL-6, CXCL8 and TNF were found in lower airways of rural Indian women who were chronically exposed to smoke from biomass compared to liquified petroleum gas during cooking [ 5 ]. Also, several proinflammatory cytokines in serum samples have been associated with biomass smoke [ 25 ]. To estimate the impact of solid fuel use on upper airway inflammation, factors listed above need to be considered in future studies, but also including contributing inflammatory activity due to NP pathogens and exposure to solid fuel use in the neighborhood [ 26 ] and at work [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results contrast to a previous study, in which higher levels of IL-6, CXCL8 and TNF were found in lower airways of rural Indian women who were chronically exposed to smoke from biomass compared to liquified petroleum gas during cooking [ 5 ]. Also, several proinflammatory cytokines in serum samples have been associated with biomass smoke [ 25 ]. To estimate the impact of solid fuel use on upper airway inflammation, factors listed above need to be considered in future studies, but also including contributing inflammatory activity due to NP pathogens and exposure to solid fuel use in the neighborhood [ 26 ] and at work [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cigarette smoke is a well known cause of COPD [31] provoking endothelial apoptosis and dysfunction [32,33]. Biomass stove smoke particularly affects women from low-income and middleincome countries [30], who may develop more severe PH [34] compared with those exposed to tobacco. Several ILDs are either strongly associated with or at increased risk from tobacco exposure [35], but its relevance to PH development is unknown, although similar effects on the endothelium may be hypothesized.…”
Section: Environmental Exposuresmentioning
confidence: 99%
“…The most studied environmental pollutants in COPD and ILD are tobacco (and in COPD, biomass smoke from household stoves [30]), airborne particulates such as nitric dioxide (NO 2 ), ozone (O 3 ), carbon monoxide (CO) and particulate matter less than 10 μm (PM 10 ) or less than 2.5 μm (PM 2.5 ). However, few studies have focused on these agents and the development of PH.…”
Section: Environmental Exposuresmentioning
confidence: 99%
“…ХОБЛ представляет собой сложное гетерогенное заболевание, характеризующееся воспалительной реакцией на хроническое воздействие вдыхаемых токсичных частиц, вызываю щих повреждение легочной ткани 2 . Для ХОБЛ характерны разрушение паренхимы, эмфизема, гиперсекреция Хронические заболевания легких слизи, сужение просвета дыхательных путей, очаговый фиброз [36].…”
Section: роль микрорнк в патогенезе и диагностике хронической обструк...unclassified